International economics - Viner, Jacob (Glencoe, Ill. : Free Press, 1951)
This is a collection of 25 essays originally published between 1924 and 1949. The book covers topics like: the most favored nations clause in American commercial treaties; the theory of international values; international finance and balance of power diplomacy; the Australian tariff; the tariff question and the economist; the theory of protection and international trade; international aspect of the gold standard; national monopolies of raw materials; German reparations once more$1 (Bthe Bretton Woods agreement; the American interest in the colonial problem; Americas lending policy; in defense of Dollar diplomacy and others. s
Includes bibliographical footnotes.
lje 22/01/2019
Loans
Keywords: Economic policy; Economic history; United States